Drugs, including alcohol, that act as risk factors for cataract, and possible protection against cataract by aspirin-like analgesics and cyclopenthiazide. Issue 11 (November 1988) - Harding, J J; van Heyningen, R
Abstract : A case-control study of cataract in Oxfordshire explored the risks and benefits associated with a variety of drugs. Steroids including the diuretic spironolactone, nifedipine, heavy smoking, and beer drinking were associated with a raised risk. On the other hand aspirin-like analgesics (paracetamol, ibuprofen, aspirin, etc. appeared to protect against cataract. Cyclopenthiazide appeared to provide a similar protection.